Pengaruh Terpaan Akun Tiktok Raffi Ahmad terhadap Gaya Komunikasi Followers - Achmad Arvian Noerdjamil; Ani Yuningsih (UNISBA Press, 2024)
Abstract. TikTok social media is an audio visual media. This media is in the form of videos and photos created with various music juxtaposed. tiktok a media that disseminates each person's creativity and uniqueness its users. This social media can make users (followers) feel happy, because of the videos they make with various music. With Each user cannot use this media just once or twice Times because they are so happy to use TikTok social media.The presence of TikTok in Indonesia began in September 2017 and went viral on Indonesia in early 2018. Get the phenomenon of using TikTok when This is in Indonesia, it seems not only the elderly or elderly people Even young people, especially babies, also play TikTok. One of them is a public figure in Indonesia named Raffi Ahmad The first content on his personal TikTok account in 2018 had 336.9 K Likes (content enthusiast), in this content Raffi Ahmad has a non-communicative style verbal, namely providing joyful dancing (movements) with his children and wife. Raffi Ahmad's TikTok followers have a tendency to follow opinions, ideas, beliefs and movements of public figures. The purpose of this research can have a phenomenon is to find out How strong is the relationship between exposure to Raffi Ahmad's TikTok account application and imitation? communication style by followers. This research uses a correlation study with main data collection through distributing questionnaires. Data analysis techniques used is multiple linear regression analysis The results of the research show that there is a positive and significant influence exposure of Raffi Ahmad's TikTok account to followers' communication style in terms of attention to communication style. Abstrak. Media sosial tiktok merupakan sebuah media audio visual. media ini berupa video dan foto yang dibuat dengan disandingkan berbagai musik. tiktok sebuah media yang menyebarluaskan berbagai kreatifitas dan keunikan setiap penggunanya. Media sosial ini dapat membuat pengguna (followers) merasa senang, karena video-video yang mereka buat dengan berbagai musik. Dengan menggunakan media tersebut setiap penggunanya pun tidak bisa hanya sekali dua kali karena begitu senang nya mereka menggunakan media sosial tiktok. Hadirnya tiktok di Indonesia diawali pada September 2017 serta jadi viral di Indonesia pada dini tahun 2018. Mendapatkan fenomena pemakaian tiktok dikala ini di Indonesia, kayaknya tidak cuma dari golongan orang berusia lansia maupun anak muda saja, apalagi anak bayi juga telah bermain Tiktok. Salah satunya publik figure di Indonesia bernama Raffi Ahmad membuat konten pertama di akun tiktok pribadinya pada tahun 2018 terdapat 336,9 K Like (penyuka konten), dalam konten ini Raffi Ahmad mempunyai gaya komunikasi non verbal yaitu memberikan joget (Gerakan) kegembiraan bersama anak dan istrinya. pengikut (followers) tiktok Raffi Ahmad memiliki kecenderungan mengikuti pendapat, ide, keyakinan, dan gerakan publik figurenya. Tujuan dari penelitian ini dapat memiliki fenomena adalah untuk mengetahui seberapa kuat hubungan terpaan aplikasi akun tiktok Raffi Ahmad dengan imitasi gaya komunikasi oleh followers. Penelitian ini menggunakan studi korelasi dengan pengumpulan data utama melalui penyebaran kuisioner. Teknik analisis data yang digunakan adalah analisis ragresi linear berganda Hasil dari penilitian menunjukan terdapat pengaruh positif dan signifikan terpaan akun tiktok Raffi Ahmad terhadap gaya komunikasi followers dari segi atensi terhadap gaya komunikasi